2021
DOI: 10.1007/s15010-021-01661-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infections in critically ill patients with SARS-2-COVID-19 infection: results of a prospective observational multicenter study

Abstract: Purpose To investigate the prevalence, incidence and characteristics of bacterial infections and their impact on outcome in critically ill patients infected with COVID-19. Methods We conducted a prospective observational study in eight Italian ICUs from February to May 2020; data were collected through an interactive electronic database. Kaplan-Meier analysis (limit product method) was used to identify the occurrence of infections and risk of acquisition. Results During the study period 248 patients were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
27
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 31 publications
10
27
1
2
Order By: Relevance
“…In addition, we used a longitudinal approach and did not focus on early infections only [ 3 , 19 ]. Nosocomial infection rate on ICU was 28% in our cohort and is in line with what has been reported before [ 20 ]. Respiratory co-infections occurred in 29.4% of all patients, most of them on IMV with an overall rate of 52.7%.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we used a longitudinal approach and did not focus on early infections only [ 3 , 19 ]. Nosocomial infection rate on ICU was 28% in our cohort and is in line with what has been reported before [ 20 ]. Respiratory co-infections occurred in 29.4% of all patients, most of them on IMV with an overall rate of 52.7%.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was a distinct possibility of the role of secondary infections in modulating the expression of three neutrophil secretory proteins in severe COVID-19 patients. Importantly, similar to the reports of higher proportion of secondary infection in patients from China ( Zhou et al., 2020 ), Italy ( De Santis et al., 2021 ), France ( Roger et al., 2021 ) and UK ( Hughes et al., 2020 ), 61% of severe patients from our study suffered from secondary infection. The observations of raised levels of these proteins much before the appearance of secondary infection ( Figures 3B–D ) provide important evidence for the association of higher expression levels of DEFA1/Calprotectin/MPO levels with COVID-19 severity.…”
Section: Discussionsupporting
confidence: 91%
“…As was previously reported [10,24], P. aeruginosa and S. aureus including MRSA, MSSA and Enterobacterales were the most common microorganisms seen in this study. A recent Italian study prospectively followed 248 patients in eight ICUs, and found 36% secondary bacterial infection, primarily VAP, with the same dominant bacteria as were reported in our study but without the use of molecular diagnostic methods [25].…”
Section: Discussionsupporting
confidence: 84%